Development of Tolerant Traits in Tea Mosquito Bug (Helopeltis Theivora Waterhouse) (Hemiptera: Miridae) under Insecticide Stress - Mukhopadhyay, Ananda; Roy, Somnath (International Journal of Bio-resource and Stress Management, 2013)
Despite continuous application of synthetic insecticides of different kinds, the sucking pest of tea, Helopeltis theivora Waterhouse (Hemiptera: Miridae) has become most damaging to tea crop in Darjeeling Terai-Dooars and North East India. In conventionally managed tea plantations, specimens of H. theivora get a regular exposure to synthetic insecticide showing significantly enhanced values of median lethal concentration or LC50. Such pesticide-stressed populations of H. theivora mainly sported changes in (i) colouration (ii) development and fitness (iii) body lipid quantity (iv)detoxifying enzyme levels and (v) egg-laying behavior implying adaptive changes of certain fitness components in the biology of the tolerant/ resistant strains. This study reveals a reduced efficacy of insecticides (viz. endosulfan, quinalphos, oxydemeton methyl, imidacloprid, monocrotophos, thiametoxam, cypermethrin and lambda cyhalothrin) against conventional field populations of H. theivora, possibly due to the changed traits in the insecticide- stressed but tolerant populations of H. theivora. Such developments throw up serious challenges for management of this major sucking pest of tea in Terai-Dooars and the North East India.